Trap-induced charge transfer/transport at energy harvesting assembly. (29th December 2016) - Cho, Seongeun; Paik, Hanjong; Kim, Tae Wan; Park, Byoungnam
Abstract: Understanding interfacial electronic properties between electron donors and acceptors in hybrid optoelectronic solar cells is crucial in governing the device parameters associated with energy harvesting. To probe the electronic localized states at an electron donor/acceptor interface comprising a representative hybrid solar cell, we investigated the electrical contact properties between Al-doped zinc oxide (AZO) and poly (3-hexylthiophene) (P3HT) using AZO as the source and drain electrodes, pumping carriers from AZO into P3HT. The injection efficiency was evaluated using the transmission line method (TLM) in combination with field effect transistor characterizations. Highly conductive AZO films worked as the source and drain electrodes in the devices for TLM and field effect measurements. A comparable contact resistance difference between AZO/P3HT/AZO and Au/P3HT/Au structures contradicts the fact that a far larger energy barrier exists for electrons and holes between AZO and P3HT compared with between P3HT and Au based on the Schottky–Mott model. It is suggested that band to band tunneling accounts for the contradiction through the initial hop from AZO to P3HT for hole injection. The involvement of the tunneling mechanism in determining the contact resistance implies that there is a high density of electronic traps in the organic side.